2010
DOI: 10.5194/bg-7-2159-2010
|View full text |Cite
|
Sign up to set email alerts
|

Marine hypoxia/anoxia as a source of CH<sub>4</sub> and N<sub>2</sub>O

Abstract: Abstract. We review here the available information on methane (CH 4 ) and nitrous oxide (N 2 O) from major marine, mostly coastal, oxygen (O 2 )-deficient zones formed both naturally and as a result of human activities (mainly eutrophication). Concentrations of both gases in subsurface waters are affected by ambient O 2 levels to varying degrees. Organic matter supply to seafloor appears to be the primary factor controlling CH 4 production in sediments and its supply to (and concentration in) overlying waters,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
240
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(263 citation statements)
references
References 180 publications
15
240
0
1
Order By: Relevance
“…However, if it is transported upwards, and not reduced during its passage through the denitrification zone, and reaches the oxic waters above, it may contribute to the general N 2 O supersaturation of the central Baltic Sea (Rö nner, 1983;Brettar and Rheinheimer, 1991). However, it appears that denitrification is able to consume most of the produced N 2 O during stable anoxic periods and that large production of mainly occurs during transition from oxic to anoxic conditions (Naqvi et al, 2010). Surprisingly Hietanen et al (2012) only found complete denitrification to N 2 and no accumulation of N 2 O.…”
Section: Regulation Of Denitrificationmentioning
confidence: 99%
“…However, if it is transported upwards, and not reduced during its passage through the denitrification zone, and reaches the oxic waters above, it may contribute to the general N 2 O supersaturation of the central Baltic Sea (Rö nner, 1983;Brettar and Rheinheimer, 1991). However, it appears that denitrification is able to consume most of the produced N 2 O during stable anoxic periods and that large production of mainly occurs during transition from oxic to anoxic conditions (Naqvi et al, 2010). Surprisingly Hietanen et al (2012) only found complete denitrification to N 2 and no accumulation of N 2 O.…”
Section: Regulation Of Denitrificationmentioning
confidence: 99%
“…A typical consequence of the local wind forcing is the fertilization of surface water column that increases primary production during the austral spring-summer (with ranged from 1.2 to 10 g C m À2 d À1 , Farías et al, 2009) and also leads to strong outgassing of N 2 O and CH 4 (Cornejo et al, 2007;Naqvi et al, 2010).…”
Section: Methane Content In the Water Columnmentioning
confidence: 99%
“…Among costal ecosystems, eastern boundary coastal upwelling areas could be major sources or hotspots of marine CH 4 (Monteiro et al, 2006;Kock et al, 2008;Naqvi et al, 2010). There, a combination of physical and biological processes must co-occur to produce high air-sea CH 4 efflux.…”
Section: Introductionmentioning
confidence: 99%
“…In the water column with low oxygen concentrations and in sediments or inside suspended particles, nitrification and denitrification can occur simultaneously and are often closely coupled (Seitzinger, 1988;Ward et al, 1989;Capone, 1991;Middelburg et al, 1996;Barnes and Owens, 1998;Naqvi et al, 1998;Robinson et al, 1998;Usui et al, 2001;Nevison et al, 2003;Codispoti et al, 2005;Bange, 2008). The yield of N 2 O from both processes is highly dependent on the concentration of dissolved oxygen (Goreau et al, 1980;de Bie et al, 2002;Naqvi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Denitrification occurs under low oxygen (o6 μmol L À 1 ) to anoxic conditions (Nevison et al, 2003). Denitrification produces and consumes N 2 O in oxygen minimum zones and the net result is that oxygen minimum zones have some of the highest N 2 O concentrations in the ocean (LaMontagne et al, 2003;Naqvi et al, 2010;Zamora et al, 2012;Arévalo-Martínez et al, 2015). In the water column with low oxygen concentrations and in sediments or inside suspended particles, nitrification and denitrification can occur simultaneously and are often closely coupled (Seitzinger, 1988;Ward et al, 1989;Capone, 1991;Middelburg et al, 1996;Barnes and Owens, 1998;Naqvi et al, 1998;Robinson et al, 1998;Usui et al, 2001;Nevison et al, 2003;Codispoti et al, 2005;Bange, 2008).…”
Section: Introductionmentioning
confidence: 99%